Os laboratórios didáticos em um curso de Física do Parfor no estado do Maranhão - Alencar, Fábio Pessoa (2016)
Traditionally, teaching physics even is facing the mechanism, developing accumulation of information and mathematical formalism of operational skills. This practice creates difficulties in the development of scientific contents, which leads most students do not identify with it, making negative outpourings. In relation to teaching physics laboratory in Brazil, can say that lived a dormant state.However, through several projects, teaching laboratories, which decrease the difficulties of student learning, back to become evident, with new methodological proposals, equipment, assemblies, and so on. Facing these motives and way of teaching and learning we think of work to assess the issue of teaching laboratories in degree courses in Physics PARFOR. With that came the following issues: What are the contributions of the curricular components for laboratories in a Degree in Physics offered by PARFOR in the training of teachers of physics? We understand that PARFOR program is of utmost importance for a science as physics, beyond that, there is a dearth of physics teachers for basic education. Thus, our objectivel was to present some theoretical aspects of teaching in the undergraduate laboratory in a Degree in Physics PARFOR. The course was analyzed the PARFOR-IFMA. We opted for this due to the fact our experience it either as a teacher or coordinator. About the type of research, we chose the methodological use of a qualitative nature; as the methodological approach, we use a case study, which establishes a strategy of research, considering the existing data with the intention of investigating them in depth, in which the main target of study may be a person or group of people. We must emphasize that, given the menus the curriculum components for laboratories of the Degree in Physics, the teacher may choose to experimental activities in which the student can act so really active menus courses.